ANALISIS EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENCAIRAN TUNGGAKAN PAJAK DI KPP PRATAMA TAHUNA - Marellu, Afke; Sondakh, Jullie J; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
One of the efforts to achieve the country's development by exploring the source of funds from domestic sources in the form of taxes but awareness of the taxpayers are less concerned in paying taxes therefore tax collection should be the goal so that taxpayers can settle their tax debt. The purpose of this study is to provide an overview of collection action with a letter of reprimand and forced letter as well as the effectiveness of tax collection with a letter of reprimand and forced letter to the disbursement of tax arrears on KPP Tahuna. In this study using a comparative descriptive. Based on the research results can be seen the level of effectiveness of tax collection by the warning letter and the letter and forced in 2012-2015 are less effective because they brought indicators of the effectiveness of 60%. Some things cause payment letter of reprimand and forced letter did not reach 100% among others existence of difficulties in finding residence address of the taxpayer, the presence of two TIN of the tax payer and the taxpayer who does not acknowledge the existence of the tax debt.Keywords: Tax Billing, Level of Effectiveness.